Post a New Question


posted by .

solve by the substitution method. 6x+3y=-21 -4x+y=41

  • algebra -

    there are so many ways of doing this problem! you can solve for x or y.
    let's solve for x.
    take -4x+y=41
    when u solve x= 1/4y-41/4
    plug that value of x into the other equation: 6x+3y=-21
    it should look like this
    6(1/4y-41/4)+3y=-21 and solve for y
    after u solve for y
    plug it in to whatever equation & solve for x and then u check it.
    you can do it vice versa & solve for y first if you want too:)

  • algebra -

    from the 2nd: y = 41-4x

    sub into the 1st:
    6x + 3y = -21
    6x + 3(41-4x) = -21
    6x +123 - 12x = -21
    -6x = -144
    x = 24

    sub into y = 41-4x = 41-4(24) = -55

    x = 24
    y = -55

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question